Prevailing food safety culture in companies operating in a transition economy - Does product riskiness matter?. (January 2020) - Nyarugwe, Shingai P.; Linnemann, Anita R.; Luning, Pieternel A.
Abstract: Food safety outbreaks are recurrent events, which regularly cost human lives. Food safety goes beyond food safety management systems; an organisation's prevailing food safety culture, and its internal and external environment must also be considered. This study introduces a research framework to analyse crucial food safety culture elements, and characteristics of the internal (i.e. food safety program, product riskiness, and vulnerability of food production system) and the external company environment (i.e. national values and food safety governance characteristics). We hypothesised that companies producing high-risk products are more likely to demonstrate a proactive food safety culture. We used the framework to assess nine companies producing low, medium, and high-risk products in Zimbabwe, as a case of a transition economy. Results showed no direct relationship between product riskiness and food safety culture, which negated our hypothesis. Other variables explored in this study could have moderated the relationship. We found that the vulnerability (i.e. susceptibility to microbial contamination) of the food production system could be associated with an organisation's food safety culture. Moreover, the external environment could have shaped the prevailing food safety culture. In particular, food safety governance and national values seem to be reflected in the way food safety was prioritised, food safety programs were designed and implemented, the prevailing food safety culture, and the observed food safety behaviour. Further research could investigate the role of the external environment in an organisation's food safety culture by evaluating companies in countries operating with different food safety governance approaches and national values. Highlights: Prevailing food safety culture seems independent of product riskiness. Food safety governance could explain the prevailing food safety culture. Multinational companies have a better food safety culture than local companies.